The performance response of a heat pipe evacuated tube solar collector using MgO/MWCNT hybrid nanofluid as a working fluid - Henein, Shady M.; Abdel-Rehim, Ahmed A. (Case studies in thermal engineering, 2022)
Utilizing a hybrid nanofluid is a promising solution for enhancing the thermal performance of the solar collector in a sustainable manner. In the present work, the effect of using magnesium oxide/multi-walled carbon nanotubes (MgO/MWCNT) hybrid nanofluid on the thermal performance of the evacuated tube solar collector is experimentally investigated. Four different weight ratios of (80:20), (70:30), (60:40), and (50:50) are used for a hybrid of MgO with MWCNTs in a water base, respectively. The experiments are performed at a 0.02% particle concentration and at various volume flow rates ranging from 1 to 3 L/min. The results show an enhancement in the energy and exergy efficiencies with the increase in the weight ratios of MWCNTs nanoparticles and volume flow rate. The enhancement of the energy and exergy efficiencies of the collector is 55.83% and 77.14%, respectively, for MgO/MWCNT (50:50) hybrid nanofluid. It is found that increasing the weight ratio of MWCNTs nanoparticles from 20% to 30% achieves a significant increase in the collector efficiency enhancement compared to other hybrid nanofluids. The results conclude that MgO/MWCNT (50:50) performs better than all other hybrid nanofluids at all volume flow rates and is closer to MWCNT/water nanofluid.